Work in Progress: Output Impedance Specification of A Three-Phase Current-Source Inverter for Modular Photovoltaic Applications - Peng Q.; Migliazza G.; Buticchi G.; Guenter S.; Tan N.M.L.; Yang J.; Wheeler P. (Institute of Electrical and Electronics Engineers Inc., 2024)
Impedance-based stability assessment has been an important part of renewable integration. Modeling and measurement of impedance under Synchronized Reference Frame (SRF) is a common way for a portrait of the frequency-dependent impedance. In this paper, a modified current-source inverter (CSI) called CSI7 for photovoltaic (PV) integration is studied. The SRF admittance of the system under different solar irradiation from 400W/m2 to 1000W/m2 with a resolution of 100W/m2 is measured in PLECS simulation. It is found that large frequency-dependent admittance appears under the high-frequency zone of the q axis which could lead to harmonic instability problems. 2023 IEEE.